Testing of the supramolecular complex of ivermectin Aniverm-2.0% against parasitosis on various types of livestock animals - M. B. Musaev; V. V. Zashchepkina; E. E. Belova; S. S. Khalikov; A. Z. Dzhamalova; I. H. Shahbiev (Российский паразитологический журнал, 2024)
The purpose of the research is to obtain and test a complex drug Aniverm-2.0% based on the ivermectin substance by free feeding in a mixture with concentrated feed against parasitosis of cattle, sheep, and horses.Materials and methods. Aniverm-2.0% obtained by mechanochemical technology was tested on a farm in the Shatoy Region, the Chechen Republic, on 900 sheep, 180 cattle and 156 horses in March-April 2023. To determine the infection rate, coproovoscopic examinations were conducted on 80 samples from sheep, 20 samples from young cattle and 30 samples from horses using the Fulleborn’s flotation method with a saturated sodium chloride solution. Sheep were dewormed using a group method. The drug was mixed with feed per 0.3 mg/kg for the AS or 60 mg for the drug per animal. The young cattle were kept by tie-up housing and therefore they were given Aniverm-2.0% once at a dose of 0.2 mg/kg for the AS individually in a mixture with feed. The horses were given the drug in a group method at a dose of 0.2 mg/kg for the AS or 1.5 mg/kg for the drug. Fecal samples from all animals were examined before and 2 weeks after the drug.Results and discussion. A 100% rate of infection of the sheep by gastrointestinal nematodes (Strongylata, Nematodirus spp., Trichocephalus spp.) was determined with an average number of eggs 633.3 in 1 g of feces. In 20 fecal samples from the young cattle, 16 were found to have Strongylata eggs (prevalence = 80.0%) with 222.2–280.5 specimens of Strongylata eggs found in 1 g of feces. Strongylata eggs were found in all 30 examined fecal samples from the horses, on average, 253.3 specimens/g of feces (100%). At 2 weeks after treatment, nematode eggs were found in three out of 80 examined fecal samples from the sheep, which can be explained that the sheep did not eat the appropriate dose of the drug. The drug efficacy was determined to be 99.7%. One hundred percent efficacy of the drug was obtained on young cattle and horses.